2015
DOI: 10.1007/s13193-015-0428-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgery in the Management for Gastric Cancer with Synchronous Distant Metastases

Abstract: Optimal treatment of patients with gastric cancer with synchronous distant metastases is palliative chemotherapy. However, occasionally gastrectomy should be selected due to control bleeding from tumors, perforation, or obstruction. The aim of this study is to evaluate the survival benefits of non-curative gastrectomy for patients with synchronous distant metastasis. Total 78 gastric cancer patients with synchronous distant metastasis treated in our hospital between 2003 and 2012 were enrolled in this study. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Some studies have shown that palliative gastrectomy obtained no survival benefit in patients with peritoneal metastases. 32 , 40 42 However, our analysis demonstrated that both peritoneal metastasis (HR=0.46, 95% CI=0.28–0.73, I 2 =61%) and hepatic metastasis (HR=0.46, 95% CI=0.33–0.65, I 2 =0%) benefited from palliative gastrectomy combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Some studies have shown that palliative gastrectomy obtained no survival benefit in patients with peritoneal metastases. 32 , 40 42 However, our analysis demonstrated that both peritoneal metastasis (HR=0.46, 95% CI=0.28–0.73, I 2 =61%) and hepatic metastasis (HR=0.46, 95% CI=0.33–0.65, I 2 =0%) benefited from palliative gastrectomy combined with chemotherapy.…”
Section: Discussionmentioning
confidence: 61%
“… 31 According to the 2009 annual conference of the JGCA, the 5-year OS was 88% in resected patients without residual tumors, 1.5% in unresected patients, and 9.9% in resected patients with residual tumors, which indicates that palliative gastrectomy could improve the survival of advanced gastric cancer patients and give them a good prognosis. 32 , 33 From another perspective, palliative gastrectomy may be beneficial for incurable advanced gastric cancer because it relieves the symptoms of advanced gastric cancer, including obstruction and bleeding, but it also prevents perforation or debilitating ascites to improve the quality of life. In addition, palliative gastrectomy can reduce the tumor burden to improve the response to adjuvant modalities and enhance the immunologic benefit due to the immunosuppressive cytokines produced by the tumor itself.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies underscore the importance of patient selection for gastrectomy considering the risk factors such as patient age and performance status [6,[12][13][14][21][22][23][24]. Based on our experience, we believe that patient age itself is not a contraindication for gastrectomy, if the performance status is satisfactory.…”
Section: Discussionmentioning
confidence: 89%
“…GC is associated with complex genetic and environmental interactions and is therefore considered to be a heterogeneous disease [ 2 ]. Despite the development of interventions such as gastrectomy and adjuvant chemotherapy, patients with GC have a poor prognosis because of the frequency of lymphatic or distant metastases [ 3 ]. Epigenetic changes are closely associated with GC invasion, metastasis, and chemoresistance [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%